Pengaruh Penggunaan Gadget Terhadap Dinamika Pergaulan Anak di Era Digital: Studi Kasus SD Negeri Bakung II Tangerang-Banten - Luki, Azis; Fitra, Candrika Nugra; Darmi; Nugroho, Dimas Putro; Inayati; Maresky, Jeky Aprilian; Wulandari, Lusi Emila; Juniandar, Rofifah; Apitasari, Pipit; Alfian, Rafi; Nitami, Shela; Anisyah, Siti; Awaliah, Siti Ila; Saputra, Teguh Darmawan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research aims to learn more about the impact of gadget use on children's social dynamics in the modern era. This research focuses on students at SD Negeri Bakung II Tangerang, Banten. Descriptive qualitative methods were used in this endeavor to gain a more comprehensive understanding of this phenomenon. Data was collected through in-depth interviews and documentation from a number of people involved, including students from grade 4 to grade 6, teachers, and parents. Individual perceptions and experiences related to device usage were studied through in-depth interviews and documentation, which supplemented the data with relevant information. The results showed that the use of the devices had significant positive impacts, including an increase in students' knowledge through access to additional information However, negative consequences were also found, such as decreased concentration in schoolwork, a tendency to become more introverted, and an increased likelihood of bullying and drug abuse among children. These results were obtained through thematic analysis of the data collected. This research utilized the triangulation method, which involves using multiple sources of data to ensure that the results are consistent. In addition, the study conducted participant testing to obtain feedback and validation on the findings and interpretation of the results. This research emphasizes how important it is for parents and teachers to supervise and teach their children to use electronic devices so that the negative effects can be reduced. It is hoped that this research will provide insights for schools, parents and policy makers in formulating effective strategies to help children's social development in the digital age, as well as encourage the creation of a healthier and more productive environment for future generations.